2020
DOI: 10.3390/ijerph17145085
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Preferences for Aging in Place Among Older Adults Living in Rural Northeast China

Abstract: The present study examines the association between cognitive social capital and structural social capital and aging-in-place among older adults living in rural Northeastern Chinese communities. Data were derived from a survey conducted in Dongliao County, Jilin Province, China, in late 2019. A quota sampling approach was used to recruit 458 respondents aged 60 years and older. Structural equation modeling was applied to test the proposed model. The results show that the measurement models of cognitive social c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A total score ranges from 0 to 7, and a higher score indicates a greater number of organizational memberships. The respondents were also asked whether they participated in volunteering activities (0 = No, 1 = Yes) and whether they participated in social activities/services in the past 3 months (0 = No, 1 = Yes) ( Lu et al, 2020 ). Supplementary Table 1 documents each measurement to construct cognitive and structural SC in detail.…”
Section: Methodsmentioning
confidence: 99%
“…A total score ranges from 0 to 7, and a higher score indicates a greater number of organizational memberships. The respondents were also asked whether they participated in volunteering activities (0 = No, 1 = Yes) and whether they participated in social activities/services in the past 3 months (0 = No, 1 = Yes) ( Lu et al, 2020 ). Supplementary Table 1 documents each measurement to construct cognitive and structural SC in detail.…”
Section: Methodsmentioning
confidence: 99%
“…However, a survey in China noted that there was a low percentage of fulfilled needs, with services provided by communities being insufficient (14), among which regular visits by professionals, referrals, and first-aid, physical examination, and education were the most sought after needs in medical demand (15). Moreover, it has been indicated that, in the United States of America, Singapore, and China, senior citizens were more willing to take care of themselves at home or in the community, bringing a better quality of life, a sense of belonging, and security, thereby achieving social value (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%